MARINE SILK ROAD: EARLY MARINE COMMUNICATIONS - Z. A. Kamalova (International Scientific and Current Research Conferences, 2022)
This article studies the history of the Maritime Silk Road since ancient times. A new interpretation was also given, which was established in the scientific literature by looking at the history of the Maritime Silk Road, from new theoretical and methodological positions. The active conduct of Maritime trade in ancient times along the Trans-Caspian route was considered. This is confirmed by archaeological material.